Establishing the impact of COVID-19 on the health outcomes of domiciliary care workers in Wales using routine data: a protocol for the OSCAR study. - Lugg-Widger, Fiona Victoria; Cannings-John, Rebecca; Akbari, Ashley; Brookes-Howell, Lucy; Hood, Kerenza; John, Ann; Jones, Hywel; Prout, Hayley; Schoenbuchner, Simon; Thomas, Daniel; Robling, Michael (International Journal of Population Data Science, 2021)
Introduction Domiciliary care workers (DCWs) continued providing social care to adults in their own homes throughout the COVID-19 pandemic. Evidence of the impact of COVID-19 on health outcomes of DCWs is currently mixed, probably reflecting methodological limitations of existing studies. The risk of COVID-19 to workers providing care in people's homes remains unknown. Objectives To quantify the impact of COVID-19 upon health outcomes of DCWs in Wales, to explore causes of variation, and to extrapolate to the rest of the UK DCW population. Methods Mixed methods design comprising cohort study of DCWs and exploratory qualitative interviews. Data for all registered DCWs in Wales is available via the SAIL Databank using a secured, privacy-protecting encrypted anonymisation process. Occupational registration data for DCWs working during the pandemic will be combined with EHR outcome data within the SAIL Databank including clinical codes that identify suspected and confirmed COVID-19 cases. We will report rates of suspected and confirmed COVID-19 infections and key health outcomes including mortality and explore variation (by factors such as age, sex, ethnicity, deprivation quintile, rurality, employer, comorbidities) using regression modelling, adjusting for clustering of outcome within Health Board, region and employer. A maximum variation sample of Welsh DCWs will be approached for qualitative interview using a strategy to include participants that vary across factors such as sex, age, ethnicity and employer. The interviews will inform the quantitative analysis modelling. We will generalise the quantitative findings to other UK nations. Discussion Using anonymised linked occupational and EHR data and qualitative interviews, the OSCAR study will quantify the risk of COVID-19 on DCWs' health and explore sources of variation. This will provide a secure base for informing public health policy and occupational guidance.